The Effect of Work Motivation, Work Environment, and Work Discipline on Employees’ Performance Of Samsat Office, Makassar - Ade Firmansyah; Haris Maupa; Idrus Taba; Hardiyono Hardiyono (Magister Management, Hasanuddin University, 2020)
The most important aspect of being an employee of performance within an organization, because it is becoming one of the determining factors in the achievement of the vision and mission of the organization. This study aimed to examine the effect of work motivation, work environment, work discipline on employees’ performance. This research was conducted in SAMSAT Office of Makassar City for two months. The types of data were quantitative data and the sources of data were primary and secondary data. The populations were all employees of SAMSAT Office of Makassar City consisting of 75 people (the police and the civil officials 51 people, dispenda 21 people, and jasaharja 3 people). All populations were taken as samples (census sampling method). They were obtained through survey. They were analyzed using validity test, reliability test, descriptive analysis, and multiple linear regression analysis. The results of the research indicate that work motivation, work environment, and work discipline have a positive and significant effect on employees’ performance. All researches hypotheses are accepted. This indicates that the increase of work motivation, work environment, and work discipline can improve employees’ performance.